A meta-analysis of effects of computer assisted education on students’ academic achievement: A-10-year review of achievement effect - Dikmen, Melih; Tuncer, Murat (Karadeniz Technical University, 2018)
The aim of this study is to determine the effect of computer-assisted education on the academic achievement of students through using meta-analysis method, defined as the interpretation of quantitative data. Meta-analysis studies are statistically analyzed for numerical data obtained from independent studies in similar subjects. Certain criteria are used to determine which researches will be included in the meta-analysis process. 43 experimental studies published between 2007 and 2017 were included in the study. As a result of the meta-analysis, the effect of computer-assisted education on student’s academic achievement was determined to be 1.028 level according to the random effect model. The effect of computer-assisted education on student’s academic achievement is found to be strong considering Cohen’s effect size range. © Karadeniz Technical University. All rights reserved.
Bilgisayar destekli eğitimin öğrencilerin akademik başarıları üzerindeki etkisinin meta-analizi: Son 10 yılda yapılan çalışmaların İncelenmesi
Keywords: Academic achievement; Computer assisted education; Effect size; Meta-analysis